THE EFFECT OF COOPERATIVE LEARNING AND STUDENT ACTIVITY ON BIOLOGICAL LEARNING ACHIEVEMENT - Wenny Okta Haryani; Bambang Sahono (DIADIK, 2019)
This study aims to examine the differences between the learning achievement of students who study with the NHT type of cooperative learning model with students who learn with the STAD type cooperative learning model, the differences in learning achievement of students who have high activeness with students who have low activeness, interaction between learning models and activeness students towards learning achievement. The design used in this study was an experimental squasi with 2 x 2 factorial designs. The study population was all students of class XI MIPA of SMA Negeri 1 Lahat in the academic year 2019-2020 consisting of 5 classes. The class used as the sample of the experimental group was class XI MIPA 1 and the control class was class XI MIPA 2. The sample selection was carried out using a purposive random sampling technique. Data were collected by learning achievement tests in the form of multiple choices and questionnaires for learning activeness. The data collected was processed statistically using a two-way variance (anava) analysis technique using a significance level of 5%. The results showed that: (1) the learning achievement of students taught using NHT type cooperative learning was higher than that of the STAD type cooperative learning model, (2) the learning achievement of students who had high learning activity scores, higher than those of students who had low activity , (3) there is an interaction between cooperative learning models and learning activeness towards learning achievement.